Factors associated with antenatal mental disorder in West Africa: A cross-sectional survey - Ola Bola; Crabb Jim; Tayo Adetokunbo; Gleadow Ware Selena H; Dhar Arup; Krishnadas Rajeev (BMC, 2011)
Abstract Background Maternal mental illness is likely to have a profound impact in less developed parts of the world. A mother experiencing mental illness in a low income setting is at risk of providing sub-optimal care for her offspring which can have grave consequences in an environment where poverty, overcrowding, poor sanitation, malnutrition, tropical diseases and a lack of appropriate medical services may be pronounced. Given the profound consequences of antenatal and postnatal mental illness on maternal mental health, foetal wellbeing and childhood growth and development the factors associated with mental illness in a Sub-Saharan setting merit clarification and investigation. Methods A prospective survey design was conducted in Lagos. Self reporting questionnaire 20 items - SRQ20 - assessed the presence of mental illness. The WHO Multi-country Study on Women's Health and Domestic Violence Questions assessed women's exposure to violence. Numerous variables potentially associated with mental illness including maternal socio-economic factors, maternal characteristics, obstetric variables and the characteristics of previous children were recorded. Direct logistic regression was performed to assess the impact of a number of variables on the likelihood of presence of mental disorder in the population. Results 189 women were surveyed. 7% met the criteria for experiencing a common mental disorder according to their score on the SRQ-20. Of variables examined only the number of female children and the presence of inter personal violence predicted being a case of mental illness (OR = 3.400; 95%CI = 1.374 - 8.414 and OR = 5.676; 95%CI = 1.251 - 25.757 respectively). Conclusions Rates of mental disorder found in our study were lower than those previously observed internationally and in Africa, perhaps reflecting stigma about disclosing symptoms. The predictive nature of violence on mental disorder is in keeping with international evidence. Our study demonstrated that exposure to inter personal violence within the last 12 months and increasing numbers of female children predict the presence of mental illness in a sample of pregnant Nigerian women. Training and education for primary health care and obstetric health workers should highlight these areas.